2002
DOI: 10.1002/dc.10178
|View full text |Cite
|
Sign up to set email alerts
|

Primary squamous‐cell carcinoma of the thyroid gland: New evidence in support of follicular epithelial cell origin

Abstract: Primary squamous-cell carcinoma (SCC) of the thyroid gland is extremely rare. We had an opportunity to treat two such cases recently. Two elderly females presented with left lobe thyroid swelling that had a history of long-standing goiter. Fine-needle aspiration (FNA) of the thyroid nodule was done in both cases. FNA cytology showed an thyroid abscess in the first, and a Hürthle-cell neoplasm in the second case. Histopathologic diagnosis was a well-differentiated squamous-cell carcinoma with an adjacent area o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 19 publications
1
61
1
2
Order By: Relevance
“…Loss of thyroglubulin in cancer cells is expected in SCC [10]. Nevertheless, in 2 cases, reported by Sahoo et al, both showed thyroglobulin staining positivity [12]. Now it is evident that the cell of origin might be from the follicular epithelium.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Loss of thyroglubulin in cancer cells is expected in SCC [10]. Nevertheless, in 2 cases, reported by Sahoo et al, both showed thyroglobulin staining positivity [12]. Now it is evident that the cell of origin might be from the follicular epithelium.…”
Section: Discussionmentioning
confidence: 94%
“…Among benign lesions, Hashimoto's thyroiditis can show squamous differentiation [24,25]. This issue, concerning the origin of SCC, has been discussed by Sahoo et al [12]. They suggested that we should expect a higher occurrence of SCC if the theory based on metaplasia was true.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Metastasis or direct extension of squamous cell carcinoma from adjacent structures such as the larynx, esophagus, or trachea is much more common. 3 Proposed etiologies for the development of PSCCT in a gland that normally does not contain squamous epithelium include squamous metaplasia of follicular epithelial cells in the face of chronic inflammation [4][5][6] , squamous differentiation of other thyroid neoplasms 7 , or the presence of embrionic rests in remnants such as the thyroglossal duct or ultimobranchial body. 8,9 Patients usually present in the 5 th to 7 th decades of life.…”
Section: Discussionmentioning
confidence: 99%
“…from metaplastic transformation of native follicular epithelia [3]. The exact etiology for primary thyroid malignancy is not known.…”
Section: Gooptu Et Al 617mentioning
confidence: 99%